EFEK KITOSAN BLANGKAS BERMOLEKUL TINGGI DENGAN PELARUT GLISERIN SEBAGAI ALTERNATIF BAHAN DRESSING SALURAN AKAR TERHADAP Candida albicans: EFFECT OF HIGH MOLECULE CHITOSAN BLANGKAS WITH GLYCERIN AS ALTERNATIVE OF ROOT CANAL DRESSING TO Candida albicans - Trimurni Abidin; Tika Ikke Ivanti (TALENTA, 2010)
Candida albicans is one of the fungal resistances and the mostly found in endodontic infections. The exsistence of this fungi is able to make colonization or a good adherance on the dentin and to form biofilm in dentinal walls. The use of dressing root canal recomended to eliminate the microorganism and Chitosan blangkas had been choosen as an alter-native dressing which originate from natural, biocompatible, characteristic of antibacteri and antifungi similiar with non-biologic material. This study was aimed to know the effect of high molecule chitosan blangkas with glicerin use Agar Diffusion Method. Paper disk (Ç¾ 6 mm) soaked by solution of high molecule chitosan blangkas with glycerin for 60 minute then put in Potato Dextrose Agar media inoculated by Candida albicans and observed after the incubation for 24 hours. In conclusion, the high molecule chitosan blangkas in each concentration tested showed the high antifungal effect. The antifungal effect would increase in high concentration. MIC (Minimum Inhibitory Concentration) of high molecule chitosan blangkas with glycerin was 0,006%.